Wickedness of Men and Women in Edith Wharton’s “Roman Fever” and Tobias Wolff’s “Hunters in the Snow”: A Thematic Study - Muhamadfahmi, Asst. Prof. Dr. Ismael; Sayakhan, Najat Ismael (Sulaimani Journal for Humanities, 2023)
Literature is the mirror that reflects human life. Authors posit imaginary characters in imaginary situations and imaginary settings; say a forest in a snowy weather or an afternoon at a restaurant terrace. They skillfully and creatively study their characters’ reactions. The aim of this research is to show the true nature of apparently civilized people who are known to be friends. In “Roman Fever” published in 1934, Edith Wharton (1862-1937) depicts her woman character Alida Slade as a Machiavellian and narcissistic woman; she jeopardizes the life of her friend only to get her out of her way and save her own marriage out of her self-love. On the other hand, Tobias Wolff (1945- ) depicts the three male characters of his short story “Hunters in the Snow” (1981) as mean and self-absorbed men who care very little for the pain (physical or spiritual) of the other. The two short stories examined in this paper provide imagined experiences that have in their folds authentic insights into some crucial aspects of life. The researchers try to answer certain questions about the type of wickedness in the human nature of each character; the difference between these men and women is the extent of their wickedness; and why the focus is on this dark side of the human being. The paper reveals that the women characters in “Roman Fever” and their male counterparts in “Hunters in the Snow” exhibit aspects of ethical indifference and narcissism coupled with meanness each towards the other within their groups despite their apparent friendship.
Keywords: Keywords Roman Fever; Hunters in the Snow; wickedness; narcissism; human nature